Efetividade das decisões do conselho administrativo de defesa econômica: revisão judicial e segurança jurídica empresarial - Silva, Denilson Moura (2022)
This research work consists of analyzing how the decisions of the Administrative Council for Economic Defense (CADE) have been accepted, observed and complied with (or not) by the economic agents that have concentration acts or conducts submitted to examination and judgment by the antitrust agency. The submission to the decision command issued by CADE and its execution, culminating with the full compliance with the measures required by the collegiate body for the defense of the economy, presents itself as a duty imposed on the economic agents that had their acts or conduct judged by the Council. The problem of the review of such decisions by the Judiciary and the discussion about the legal security that is sought to be achieved in the scenario in which the economic players play their roles as producers of goods and wealth is what will be studied in this simple academic work. Thus, this paper has the purpose of reviewing the bibliography on competition law and CADE's performance, as well as to present some of the Judiciary's responses when asked to manifest itself in reviewing CADE's decisions and the evolution of such judicial manifestations in order to verify the level of security for the performance of the business activity aimed at the promotion of human welfare and the environment by the maximum productive and sustainable efficiency.